PENGARUH SYSTEM CREDIT POINT TERHADAP KEDISIPLINAN SISWA MA DI PONDOK PESANTREN KHAIRUL UMMAH BATU GAJAH KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU RIAU - Neni Minarti; Andrizal Andrizal; Zulhaini Zulhaini (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
This study has several objectives for researchers the selver as well as for other students inclording how much influence the System Credit Point has on the discipline of students culture especially in MA PondokPesantrenKhairulUmmah ,KecamatanPasirPenyuKabupaten Indragiri Hulu. The type of research is quantitative, namely date collection by means of observation, interviews and questionnaires, while date analysis uses product moment correlation. Besed on the results of the study of the influence of the System Credit Points in the PondokPesantrenKhairulUmmahKecamatanPasirPenyu, Kabupaten Indragiri Hulu. at the MA level this can be proved that the effect of the credit Point system (Variabel X ) and ( Variabel Y ) Is that there is a relathionship to student discipline with the correlation coefficient is equal to 0,625. The results of the research date have answered the effect between the x and y factors besides that there are several on then factor that influence it between attitudinal, factors teacher, factors facility, factors educational norms.